2018
DOI: 10.1007/s13760-018-0929-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ultrasound-guided botulinum toxin type-A injections with a specific approach in spastic cerebral palsy

Abstract: The aim of this study was to detect effects of ultrasound-guided botulinum toxin type-A (US-guided BoNT-A) injections prepared according to lower extremity innervation zones on spasticity and motor function in 3-16 years children with diplegic and hemiplegic spastic cerebral palsy. This study included 25 patients between 3 and 16 years of age who admitted to our clinic in 2017, were being followed in our clinic with a diagnosis of cerebral palsy, had BoNT-A injections due to lower extremity spasticity. The US-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…111,[139][140][141][142][143][144][145][146][147] Table 1 demonstrates many of the most commonly injected muscles. Two studies have demonstrated efficacy in using this approach for BoNT injections in both the CP population and adult stroke 148,149 ; however, there are no studies that compare this method to other techniques.…”
Section: Comparison Studiesmentioning
confidence: 99%
“…111,[139][140][141][142][143][144][145][146][147] Table 1 demonstrates many of the most commonly injected muscles. Two studies have demonstrated efficacy in using this approach for BoNT injections in both the CP population and adult stroke 148,149 ; however, there are no studies that compare this method to other techniques.…”
Section: Comparison Studiesmentioning
confidence: 99%
“…BoNT-A can be injected into the spastic muscle by palpation, electromyography (EMG), electrostimulation (ES), or under ultrasound (US) guidance [13]. Under US and EMG guidance, the injections are 90-99% effective even in small muscles [14]. However, because the injection in EMGguided infusion is painful, it is usually performed under general anesthesia for adults and children.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the nonprogressive course of the disease, children with CP require continuous dynamic observation, conservative treatment, and timely orthopedic treatment because of their neurological symptoms and concomitant secondary disorders of the musculoskeletal system (e. g., joint contracture, joint dislocation, bone torsion, and changes in the ligamentous apparatus) in the ontogenesis of motor development [5,6]. The following main groups of therapeutic effects have been distinguished by the European Consensus for the treatment of CP: oral antispastic pharmacotherapy, orthopedic surgery, botulinum therapy, intrathecal baclofen, orthotics, and functional therapy (including physiotherapy) [7]. Orthopedic surgery is necessary for the treatment of secondary joint contracture and skeletal deformities in patients with CP [8].…”
mentioning
confidence: 99%